2022
DOI: 10.1021/acs.energyfuels.2c03517
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Nitrogen-Doped Graphene: Structure Characterization, Growth Strategy, and Capacitive Energy Storage

Abstract: Nitrogen-doped graphene (NG), as an important emerging nanomaterial, exhibits superior electrical conductivity, large specific surface area, and improved hydrophilicity and has received much attention. In this review, we summarize the influence of N on the structures and properties of the graphene lattice, the key factors of NG controllable preparation, and the synthesis methods and characterization techniques. In particular, we discuss the mechanisms of N configuration and content, electrical conductivity, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Apparently, the present conversion technology could not only eliminate waste-containing cyano-organics or amino-organics but could also produce N-CNTs with a high doping ratio of N-species in situ. As indicated in refs , , these N-CNTs would be attractive as electrodes of supercapacitors or as adsorbents with hydrophilic surface properties and excellent electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the present conversion technology could not only eliminate waste-containing cyano-organics or amino-organics but could also produce N-CNTs with a high doping ratio of N-species in situ. As indicated in refs , , these N-CNTs would be attractive as electrodes of supercapacitors or as adsorbents with hydrophilic surface properties and excellent electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…38 Nitrogen groups play a crucial role in improving supercapacitor performance. 39,40 A nitrogen functionality within the carbon lattice is known to be more stable compared to embedded oxygen functional groups. Besides improving the wettability and electrochemically active sites, the presence of nitrogen-containing compounds contributes to pseudocapacitive effects (e.g., pyridine, pyrrole) in (aqueous) supercapacitors.…”
Section: Scanning Electron Microscopy and Transmission Electron Micro...mentioning
confidence: 99%
“…), which renders N-doped graphene (N-G) as arguably one of the best options for developing graphene-based electrochemical materials. Moreover, through experimental, theoretical, and computational investigations, it has been demonstrated that the introduction of nitrogen atoms into the graphene structure generates electronically active sites, enabling the material to facilitate electrochemical activities [18][19][20][21][22][23][24]. Although the primary objective of N-G-based materials is to replace precious metal-based materials, like platinum group metals (PGMs), in electrochemical applications, significant improvements in various electrochemical parameters are still required at their current developmental stage to effectively utilize N-G materials in electrochemical energy systems.…”
Section: Introductionmentioning
confidence: 99%